Development of Complex of General Development and Special Exercises - Abdirakhmon Rakhmatovich Beknazarov (Web of Journals Publishing, 2023)
The article discusses how to develop different sports abilities of boxers. It gives definitions to the terms related to development of speed, strength, endurance, and provides some practical ways to improve sports fitness.
Keywords: physical training, physical development exercises, special exercises, strength development, speed development, developing endurance, fitness, dynamic power.